Special conference to which all districts in England, Scotland and Wales were invited, held in the primitive methodist school-room, Prudhoe Street, Newcastle-on-Tyne, on Thursday and Friday, July 12th and 13th, 1894 - Miners' Federation of Great Britain
Mention de couv. : "Private" [document interne]